MEDIA EXPOSURE, COMPREHENSION, AND COMPLIANCE WITH CLIMATE-CHANGE MESSAGES AMONG RESIDENTS OF ENUGU METROPOLIS. - Victor Okeke, Somtochukwu; N. Ezugwu, Martins; Faith Nnaji, Ozioma (African Journal of Social and Behavioural Sciences, 2024)
Environmental issues have been a major worldwide problem, and Nigeria is not exempted from this problem as the country experiences flooding, erosion and other consequences of climate change. This study examines the exposure to climate change media messages and compliance with climate change media messages among residents of Enugu metropolis. The researcher adopted the survey design with a sample size of 385, which was obtained using the Australian sample size calculator. The instrument for data collection was the questionnaire. Data were analysed quantitatively using frequency, percentage, and mean and standard deviation. Findings from the study revealed that Enugu metropolis residents have high levels of exposure to climate change media messages and compliance with climate change media messages, respectively. The study recommends, among others, that a similar study should be carried out in rural areas since this study, which was conducted in an urban area with a high literacy level, looks positive with regard to exposure to climate change media messages and compliance with climate change media messages.